Pengaruh Budaya Organisasi Terhadap Produktivitas Pegawai di Universitas Ekasakti - Fatimah Azzahra; Irsyad Irsyad; Ahmad Sabandi; Merika Setiawati (CV. ITTC INDONESIA, 2026)
The importance of organizational culture in improving employee productivity has become a crucial issue in achieving organizational goals. This study aimed to determine the effect of organizational culture on employee productivity at Ekasakti University and to measure the extent of its contribution to employee productivity. Method: This study employed a quantitative approach using a correlational method. The population consisted of 83 employees, with a sample of 79 employees selected through proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire and analyzed through simple linear regression. Results: The findings showed that organizational culture had a positive and significant effect on employee productivity, with a correlation coefficient (R) of 0.887, indicating a very strong relationship. The coefficient of determination (R²) was 0.787, meaning that organizational culture contributed 78.7% to employee productivity, while 21.3% was influenced by other factors outside the study. Organizational culture and employee productivity were both categorized as high, with percentages of 90% and 88%, respectively. Novelty: This study provides empirical evidence regarding the substantial contribution of organizational culture in enhancing employee productivity within the higher education environment, particularly at Ekasakti University.